When Inefficiency Begets Efficiency - Hans Gersbach; Hans Haller (Center for Economic Studies and ifo Institute (CESifo), 2004)
Collective consumption decisions taken by the members of a household may prove inefficient. The impact on market performance depends on whether household inefficiencies are caused by inefficient net trades with the market or by inefficient distribution of resources within households. Inefficient internal distribution always results in inefficient equilibrium allocations. This leads us to consider competitive forces as a disciplinary device for households. Competition of households for both resources and members can eliminate or reduce inefficient internal distribution.
Keywords: 330